Atividade antiinflamatória, cicatrizante e antimicrobiana do extrato aquoso de aroeira-do-Sertão a 20% (myracrodruon urundeuva fr. All.) Aplicado em fraturas expostas induzidas em mandíbula de coelho - Mello, Manoel de Jesus Rodrigues de (2007)
Controlling bone healing is of great importance to traumatology, since some of the guiding principles of this area are the cleaning of the wound, the early fixation of the fracture, to assure the viability of the bone supply, and prevent the infection, especially in exposed fractures. The Aroeira-do-Sertão (Myracrodruon urundeuva Fr.All), tree of Anacardiceae family, is known for its popular uses as anti-inflammatory due to its healing activities, being a good therapeutic alternative. To investigate these properties we analyzed an experimental model using induced exposed fractures in rabbit jaws. Thirty white New Zealand male rabbits weighing between 1700 and 2100g, divided in two groups of fifteen animals each were used. The rabbits underwent surgical procedure under general anesthesia to fracture their right mandibular body, which was exposed to oral cavity for 4 hours. Material from the fracture site was collected for microbiological analysis. The animals were randomly distributed according to the proposed treatment. In Group I, 300ml of aqueous extract of Myracrodruon urundeuva at 20% was used for the irrigation of the focus of the fracture for 5 minutes. In Group II, sterile saline solution 0.9% at the same volume was used at the same way as Group I. All animals underwent fracture reduction with internal rigid fixation using 1,5mm titanium mini-plates. Before euthanasia, postoperatory radiographs were done by subgroups at 7, 14, and 30 days for analysis of the consolidation of the fractures, after which the bone fragment of the operated region was removed for histological analysis using the Masson Tricromic method. The animals were analyzed from the clinical, radiological and histological perspectives. The clinical analysis consisted in the visual verification of the aspect of the surgical wound. Group I (Myracrodruon urundeuva) showed a little improvement in healing when compared to Group II. Radiographically Groups II did not presented significant effects in the consolidation of the bone. Histologically reduction of the bacterial concentration was showed in the fracture in the Group I. The conclusion was that a Myracrodruon urundeuva aqueous extract at 20% has no significant effect in the consolidation of induced exposed fractures of rabbit jaws, but shows benefits in the healing of wounds, reducing the colonies of bacteria in the fractures sites significantly.